Klasifikasi Sentimen Ulasan Aplikasi WhatsApp di Play Store Menggunakan Naive Bayes Classifier - Yolanda, Khovifah; Yusra, Yusra; Fikry, Muhammad (J-INTECH (Journal of Information and Technology), 2023)
Currently, people can easily make remote contact with the WhatsApp application which makes it easier for users to communicate such as sending text messages, pictures, videos, voice messages, sharing files to make voice and video calls for free with internet access. WhatsApp is a digital application that can be used by the public for free, users can also provide reviews through the Google Play Store. The reviews on the Google Play Store are the opinions of users in providing input to application developers. This test aims to ascertain consumer opinions or emotions towards the WhatsApp application by applying the Naïve Bayes Classifier method in the process of classifying consumer reviews which will be used to solve for the highest score. The reviews are divided into two labels, namely positive reviews and negative reviews. Based on the tests that have been carried out, the highest accuracy results are obtained at a ratio of 90:10 with an accuracy of 81%, 74% precision and 54% recall with an unbalanced number of datasets, namely 669 positive reviews and 331 negative reviews. negative sentiment.